Maternal Forced Swimming Reduces Cell Proliferation in the Postnatal Dentate Gyrus of Mouse Offspring - Wasinski, Frederick; Estrela, Gabriel R.; Arakaki, Aline M.; Bader, Michael; Alenina, Natalia; Klempin, Friederike; Araújo, Ronaldo C. (Frontiers in Neuroscience, 2016)
Physical exercise positively affects the metabolism and induces proliferation of precursor cells in the adult brain. Maternal exercise likewise provokes adaptations early in the offspring. Using a high-intensity swimming protocol that comprises forced swim training before and during pregnancy, we determined the effect of maternal swimming on the mouse offspring’s neurogenesis. Our data demonstrate decreased proliferation in sublayers of the postnatal dentate gyrus in offspring of swimming mother at postnatal day (P)8 accompanied with decreased survival of newly generated cells 4 weeks later. The reduction in cell numbers was predominantly seen in the hilus and molecular layer. At P35, the reduced amount of cells was also reflected by a decrease in the population of newly generated immature and mature neurons of the granule cell layer. Our data suggest that forced maternal swimming at high-intensity has a negative effect on the neurogenic niche development in postnatal offspring.